2018
DOI: 10.3390/s18030757
|View full text |Cite
|
Sign up to set email alerts
|

A Context-Aware Indoor Air Quality System for Sudden Infant Death Syndrome Prevention

Abstract: Context-aware monitoring systems designed for e-Health solutions and ambient assisted living (AAL) play an important role in today’s personalized health-care services. The majority of these systems are intended for the monitoring of patients’ vital signs by means of bio-sensors. At present, there are very few systems that monitor environmental conditions and air quality in the homes of users. A home’s environmental conditions can have a significant influence on the state of the health of its residents. Monitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…In this regard, ICT solutions of smart homes for the elderly population may be categorized in relation to the context of use: (1) resident activity monitoring [36]- [46] and (2) resident health monitoring and/or managing [38], [44], [47]- [57]. They give older adults the opportunity to use wearables and/or environmental sensors and devices which are intended to monitor and/or manage various health conditions, i.e., ischaemic heart disease [47], stroke [39], [49], [50], [58], Alzheimer's disease and other dementia [4], [34], [36], [37], [41]- [46], [48], [59], chronic obstructive pulmonary disease [34], [52], [53], [60] diabetes mellitus [38], [55]- [57], and physical disabilities [51]. With this approach they can improve the coordination among caregivers, emergency response teams, and intervention effectiveness, which contributes to cost savings and better QoL for older people living with chronical conditions.…”
Section: Best Practices For Health-related Ict Solutionsmentioning
confidence: 99%
“…In this regard, ICT solutions of smart homes for the elderly population may be categorized in relation to the context of use: (1) resident activity monitoring [36]- [46] and (2) resident health monitoring and/or managing [38], [44], [47]- [57]. They give older adults the opportunity to use wearables and/or environmental sensors and devices which are intended to monitor and/or manage various health conditions, i.e., ischaemic heart disease [47], stroke [39], [49], [50], [58], Alzheimer's disease and other dementia [4], [34], [36], [37], [41]- [46], [48], [59], chronic obstructive pulmonary disease [34], [52], [53], [60] diabetes mellitus [38], [55]- [57], and physical disabilities [51]. With this approach they can improve the coordination among caregivers, emergency response teams, and intervention effectiveness, which contributes to cost savings and better QoL for older people living with chronical conditions.…”
Section: Best Practices For Health-related Ict Solutionsmentioning
confidence: 99%
“…The above test demonstrated that the HA-GN-MWCNT sensor has the required performances for monitoring CO 2 present in a closed ambient environment such as a bedroom, where base CO 2 levels are expected to increase as a result of human occupancy and could exceed that recommended for children to safely sleep [4,39].…”
Section: Resultsmentioning
confidence: 99%
“…A system intended to prevent sudden infant death which additionally to other data observes the indoor air quality is presented by De La Iglesia et al in [18]. To observe several gas concentrations multiple low-cost gas sensors based on the MOS (Metal Oxide Semiconductor) principle are used which are interfaced by an ESP8266 microcontroller.…”
Section: Systems Monitoring Indoor Air Qualitymentioning
confidence: 99%